Šalda’s Struggle for Synthesis in Modern Art in the Context of Slavonic Literary Criticis - Vorel, Jan (Bohemistyka, 2023)
The study is focused on a significant feature of critical and art work of František Xaver Šalda, which was the idea of unity and integration, the idea of cultural organism, formed by ripening of the European spirit, understanding the art as an aesthetic incarnation of spirituality, the idea of creative efforts of life as the basic orientation of art and the idea of freedom of the art individuality, understood in the integral sense of the word and embodying a higher form of life. It was Šalda who opened the way to relating of art and life, the way to deeper understanding of art creation and its final settling into a broader meaning complex. According to Šalda, the creative life became a basic criterion for searching of sense of art work. The meaning of art and art criticism lies in their possibilities to bring life to self-awareness, self-understanding. According to Šalda the art is seen as a concentrated, multiplied, and increased demonstration of life, through its means we can finally learn about its motion and creative direction.